Single-Photon Reflectivity and Depth Imaging by Continuous Measurement of Arrival Time of Photons - Qiurong Yan; Dan Li; Yifan Wang; Yibing Yang; Linao Tang; Yuhao Wang (IEEE Photonics Journal)
We demonstrate a reflectivity and depth imaging Lidar system based on a novel photon arrival time measurement method. In this method, the arrival time of photons in a scanning position is continuously measured with a common starting point. The number of laser pulses is counted by a specially designed field programmable gate array (FPGA) control module as the coarse time of arrival photon. Time interval between arrival photon and the nearest coming laser pulse is measured by a time-correlated single-photon counting (TCSPC) module as the fine time of arrival photon. Using the system, not only the single-photon counting imaging can be realized, but also the first photon imaging, the first two photons imaging, etc. can be realized. A photon statistical model based on the doubly stochastic Poisson point processes, a time-gated filtering algorithm, and the reflectivity algorithm based on maximum likelihood estimation are derived. High-sensitivity reflectivity and depth imaging with a resolution of 512 × 512 pixels are achieved. The experimental results show that the horizontal spatial resolution is 2 mm, the vertical depth resolution is 5.375 cm, and the average number of photons per pixel is less than 1.3 photons.